KALIMAT INVERSI DALAM BAHASA KAILI - Deni Karsana (Balai Bahasa Sulawesi Tengah, 2014)
Discussion of sentences of a language interesting to study. Language can be sentences composed of words that is regularly and contains a complete thought. Discussion of sentences that characterizes a language needs to be developed. Sentence inversion in Kaili language be analyzed in this paper. The method used in this paper is a descriptive method. The results of this paper, there areseveral patterns of inversion sentences in Kaili language namely (1) inversion sentence which has core structure such as predicate and subject, (2)inversion sentence which has core structure such as redicate, object, and subject, (3)inversion sentence which has core structure such as predicate,object, and subject, (4) inversion sentence which has core structure such as predicate, object, complement, and subject, and (5) inversion sentence which has core structure such as predicate,reference, and subject.